TcPO2 as a Predictor of Limb Salvage or Amputation in Patients of Critical Limb Ischemia - Rahul Merkhed; Vikram Patra; Rishi Dhillon; Rohit Mehra; CVNM Dattatreya; Ramandeep Kaur; Gagandeep Singh Vohra; Surjeet Dwivedi (Indian Journal of Vascular and Endovascular Surgery)
Introduction: Critical limb-threatening ischemia presents a significant challenge in clinical management, often necessitating lower limb amputation if not managed promptly and effectively. A crucial aspect of managing CLTI involves determining the optimal level of amputation to maximize post-surgical healing and functional outcomes. Among various non-invasive diagnostic tools, Transcutaneous Oximetry (TcPO2) has garnered attention, yet a consensus on predictive cutoff levels remains elusive in the literature. Aim and Objective: This study addresses this gap by investigating the predictive utility of TcPO2 in assessing healing outcomes following amputation or ulcer management, aiming to provide valuable insights for clinical practice and enhance patient outcomes in CLTI management. Methodology: It was conducted at a tertiary care centre in North India . Our study of 128 patients examines TcPO2 as a predictor for ulcer or amputation stump healing. By applying a cutoff of 40 mmHg, informed by previous retrospective studies suggesting its predictive efficacy, our approach seeks to standardise decision-making and optimise tissue oxygenation to improve clinical outcomes. Results: We found that a TcPO2 cutoff of 40 mmHg or higher significantly correlated with increased healing likelihood, whereas values below this threshold, particularly in patients with diabetes mellitus (DM) and chronic kidney disease (CKD), posed greater risks of non-healing outcomes. Discussion And Conclusion: This underscores the critical role of TcPO2 in assessing vascular compromise, especially in cases where conventional methods like ankle-brachial pressure index (ABPI) may be unreliable due to arterial calcifications. In our analysis, CKD and TcPO2 < 40 emerged as independent predictors of non-healing ulcers or stump in univariate regression. Interestingly, DM did not show a significant association with non-healing outcomes in this context. Moreover, in multivariate analysis, DM, CKD, and TcPO2 < 40 retained their significance as predictors of poor healing, with TcPO2 < 40 demonstrating the strongest association. Further prospective studies are warranted to validate these findings and establish robust correlations between TcPO2 values and clinical outcomes. Additionally, exploring the influence of various comorbidities and demographic factors could refine predictive models, offering tailored interventions for patients with CLTI.